Uncovering the Past Through the Lens of Justice in Dürrenmatt’s The Visit - Keleş, Aybike (Trakya Universitesi Edebiyat Fakultesi Dergisi, 2025)
Epic theatre, a form of theatrical expression, aims to stimulate critical thinking among its audience by addressing social issues and political messages. Following WWI, Brecht developed a new theory of theatre that focuses on feelings, thoughts, and human psychology. Set in the town of Guellen, the play called The Visit revolves around the arrival of Claire Zachanassian, a millionaire who returns to her hometown seeking justice for the wrongs inflicted upon her in the past. This play is presented in a way that impedes the audience’s emotional engagement while tackling society’s problems of cruelty, greed, and injustice. By employing techniques such as the alienation effect, nonlinear narrative structure, and minimal set design, this play disrupts traditional theatrical conventions and prompts the audience to question social norms. Dürrenmatt often incorporates dialogue breaks, scene gaps, and music to blur the boundary between audiences and the players. Stage settings, dialogues of characters, and employment of epic techniques not only transports the audience to a corrupt society but also conveys deep social decay. By challenging conventional narrative structures, this genre of theatre fosters a deeper understanding of the social and political implications embedded. This research will employ Brecht's epic theatrical methods to analyze this work.